Strategi Inklusi Keuangan Dengan Menilai Dampak Sistem Finpay Terhadap Penjualan Kayu Pada KBM Komersial Kayu Jawa Tengah - Fajrinnisa Pranandavin; Sutrisno Sutrisno (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
The aim of this research is to determine the implementation of the financial inclusion system through digital payments as well as the role and contribution of the Finpay application in the company's wood sales operations. This type of research is descriptive research which uses two data sources, namely, primary data by collecting data by conducting direct and indirect interviews by supervisors and secondary data by using literature as a reference in the discussion. The data source for this research was obtained by data collection methods, using interview methods and documentation methods. The research results show that the existence of Finpay and TokoPerhutani can help companies to run more efficiently than having to do it by auction and cash payments. Finpay's role in the sales and transaction process in the company has had a positive and significant impact on the company's operations so that the company can rely on Finpay as a careful monitor of every transaction and sale made by customers.